A STUDY ON THE CORE CURRICULUM OF ACCOUNTING AS THE COMPETENCIES BUILDER OF THE ACCOUNTING GRADUATES (A Study on The Accounting Graduates Who Work at Private Companies, State Companies, Non-Profit Organizations, And Public Accountant Firms in Surabaya) - Zuhroh, Diana; Parawiyati, Parawiyati; Lisetyati, Eni (Journal of Indonesian Economy and Business, 2009)
As generally known accounting graduates are considered to have low quality. BasedÂ on recent studies and practitioners experience, there are two reasons for this: (1) accountingÂ curriculums are not matched with up to date practices, and (2) they were not introducedto real practices that they will face when they have finished their study. The objectiveÂ of this study are (1) to obtain an empirical evidence about accounting practitionerÂ competences, and (2) establishing a curriculum structure that is relevant with user needs.The study used and are sent questionnaire to two hundreds respondents (accountingÂ practioners) in Surabaya. They asked to rate on one to five point Likert type scale theÂ importance of accounting competents (in knowledge, skills, and ethics), and theÂ importance of subjects needed in developing these competencies as well. The subjectsÂ listed based on goverment regulation No. 232/U/2000 and UU No. 045/U/2002. The scaleÂ is set low importance to one and high importance to five rating.This paper reports competencies and subjects listed on detail ranked in order of meanÂ score. Competences and subjects with higher rank are needed in today practice. TheÂ Accounting Department is suggested to use this result in designing its curriculum forÂ reducing gap between practice and education and to improve accounting graduatesâÂ quality.Keywords : Competency, Curriculum , Accounting Education, Accounting Graduates.